PENGARUH EKSTRAK TANAMAN DAN PREDATOR TERHADAP PENGENDALIAN ORGANISME HAMA DAN PENYAKIT UTAMA PADA TANAMAN CABAI - Neni Gunaeni; Redy Gaswanto; Astri Windia Wulandari; Eli Korlina (Gunung Djati Conference Series, 2023)
The use of plant extracts and predators is an alternative for pests control and disease that are safe for the environment. The aim of this research is to find out plant extracts and predators in controlling major pests and diseases effectively. The research was conducted at the Indonesian Vegetable Research Institute at an altitude of 1250 m above sea level from June to December 2018.The design used was Randomized Block Design and was repeated 4 times. Tried treatment: (A). Spinach (Amaranthus spinosus) extract. (B). Four o'clock flower (Mirabillis jalapa). (C). Given the predator Menochillus sexmaculatus at the beginning of planting. (D). Synthetic insecticide with the active ingredient Immidaclorprid. (E). Spinach spinach extract + predator. (F). Four o'clock flower extract + predator. (G). Spinach Extract + Predator + Insecticide. (H). Four o'clock flower + predator + Insecticide. (I). Control. Research results: (1). Plant growth is not affected by treatment. (2). Phytotoxic symptoms due to treatment of plant extracts did not appear in plants. (3). The treatment of giving predatory M. sexmacullatus at the beginning of planting + insecticide, combination of spinach thorn extract + predator + insecticide, combination of four o'clock flower extract + predator + insecticide, increased its efficacy against chili pests and diseases and had an impact on low fruit diseases and increased yields.